Analysis of IP-ICT, PDRB, UMP, and PMA on the Human Development Index in Indonesia - Saddam Bintang Raharjo (Jurnal Ilmu Ekonomi JIE, 2024)
Indonesia has abundant natural resources but has not yet become a country with high-quality human resources. Several variables were selected in the research to improve the quality of human resources linearly with natural resources. This research aims to see the influence of ICT-DI, GRDP, Minimum Wage, and FDI variables on HDI in Indonesia. This research uses a quantitative approach; the data sources are taken from the Central Statistics Agency and the Ministry of Manpower for 2020-2022, and the analysis technique used is panel data regression. The research results show that the variables ICT-DI, GRDP, Provincial Minimum Wage, and FDI significantly affect HDI in Indonesia. Meanwhile, partially, the ICT-DI variable has a significantly positive impact on HDI, the GRDP variable has a significantly positive effect on HDI, the UMP variable has no significant positive impact on HDI, and the FDI variable has a significantly positive effect on HDI